From Contagion to Control: An Examination of the Oppressive but Effective Use of Tuberculosis Sanatoriums Prior to the Implementation of Antibiotics - Jones, Calley J. (My University, 2017)
This paper examines the treatment methods of the infectious disease Tuberculosis. It begins by giving a brief history of the disease and its extreme relevance to society today. The paper then discusses the major treatment methods used during the time span of 1880-1940, prior to the implementation of Germ Theory and before the use of antibiotics. During that time there were two mainstream treatment methods: homemade elixirs and sanatoriums, homemade elixirs contained highly random and often toxic ingredients. Individuals who would be considered charlatans in today’s society sold them. The second and most effective technique for treating tuberculosis prior to antibiotics was sanatoriums. In their infancy they faced numerous tribulations that made them unappealing to the general population, and people in lower socioeconomic statuses. As public health concerns, governmental assistance, and medical knowledge increased, as did life in a sanatorium. Sanatoria would eventually prove to be the most effective and humane method to treating tuberculosis.
Keywords: Tuberculosis -- Prevention & control -- United States; Tuberculosis -- Hospitals; Tuberculosis -- History; Mycobacterium tuberculosis